2005
DOI: 10.1152/ajpcell.00115.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of delayed rectifying K+ channels in anterior rat taste buds

Abstract: Liu, Lidong, Dane R. Hansen, Insook Kim, and Timothy A. Gilbertson. Expression and characterization of delayed rectifying K ϩ channels in anterior rat taste buds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…The DRK channels are comprised of at least nine different isoforms within three different subfamilies. Rat fungiform papillae express three of them, i.e., KCNA, KCNB, and KCNC (111). Only the KCNA channels were exclusively sensitive to PUFA (111).…”
Section: Drk Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DRK channels are comprised of at least nine different isoforms within three different subfamilies. Rat fungiform papillae express three of them, i.e., KCNA, KCNB, and KCNC (111). Only the KCNA channels were exclusively sensitive to PUFA (111).…”
Section: Drk Channelsmentioning
confidence: 99%
“…Rat fungiform papillae express three of them, i.e., KCNA, KCNB, and KCNC (111). Only the KCNA channels were exclusively sensitive to PUFA (111). A combination of kinetic, pharmacological, and quantitative expression approaches have revealed that the KCNA5 isotype, also termed Kv1.5, is the major DRK channel in rat TBC (111).…”
Section: Drk Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, both receptors are sensitive to PUFAs (i.e., linoleic acid), they are located on different types of taste cells (Type I and Type II, respectively) (5). Numerous studies have demonstrated the importance of delayed rectifying potassium (DRK) channels in detecting the presence of fatty acids, particularly PUFAs (14,25). The most frequently studied fatty acid receptor thus far is CD36.…”
mentioning
confidence: 99%
“…They can realize taste information processing, such as the chemical-electrical signal transformation in taste sensation. Studies indicated that taste receptor cells could produce action potentials, elicited by sour [1] , sweet [2,3] , bitter [4] and salty [5] tastants. The analysis of the features extracted from the elicited action potentials demonstrated that the firing patterns might be utilized in taste coding [6] .…”
Section: Introductionmentioning
confidence: 99%